Targeted educational program improves infant positioning practice in the NICU. (8th June 2018) - Charafeddine, Lama; Masri, Saadieh; Ibrahim, Perla; Badin, Daniel; Cheayto, Salam; Tamim, Hani
Abstract: Quality problem or issue: Infant positioning may interfere with neuromotor development. Bedside education and Infant Positioning Assessment Tool (IPAT) improve nurses' and doctors' proficiency in applying proper infant positioning. Initial assessment: Nursing compliance with proper positioning is suboptimal due to many factors. One factor was the inadequate knowledge and practice of infant positioning, since the baseline mean IPAT score was 3.4. Choice of solution: Three experienced neonatal intensive care unit (NICU) nurses were chosen as position champions to help other NICU nurses apply proper positioning and monitor IPAT scores. Education and hands-on demonstration sessions were developed based on the observed baseline practice. Implementation: Periodic education with hands-on demonstration was given to NICU nurses and residents. Infants' positions were objectively scored using IPAT. Two Plan, Do, Study and Act cycles were completed and adjustments were made based on each cycle's achieved results. Evaluation: Mean IPAT scores increased from 3.4 at baseline and 6.3 in the second cycle to 7.3 in the third cycle of intervention. Lessons learned: A systematic approach targeting infants' positioning succeeded in improving nurses' and residents' clinical performance. Not reaching significant change until after 18 months highlights the difficulty and complexity in changing behaviors.